2014
DOI: 10.2174/1570163811666140127123717
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cyclooxygenase Inhibitors: Current Status

Abstract: For ages aspirin has established its value as an analgesic, anti-inflammatory drug, but in 1938, it was found to be a causative factor of gastric inflammation (ulcer). Later discovered non-steroidal anti-inflammatory drugs (NSAIDs) were found effective as aspirin but failed to overcome the goal of safer aspirin. As the method of prostaglandin inhibition through COX is a common mechanism to both the wanted and unwanted effects of aspirin and non-aspirin NSAIDs, the COX enzyme becomes a target for drug designers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Although aspirin is considered to be a specific inhibitor of PGs synthesis, its effect on COX is still controversial in different cell lines and its broad pharmacological effects may be associated through the regulation of redox metabolism, cell signaling and mitochondrial functions [14][15]. We, therefore, have studied the effects of LPS stimulation on murine macrophage J774.2 in conjunction with ASA.…”
Section: Introductionmentioning
confidence: 99%
“…Although aspirin is considered to be a specific inhibitor of PGs synthesis, its effect on COX is still controversial in different cell lines and its broad pharmacological effects may be associated through the regulation of redox metabolism, cell signaling and mitochondrial functions [14][15]. We, therefore, have studied the effects of LPS stimulation on murine macrophage J774.2 in conjunction with ASA.…”
Section: Introductionmentioning
confidence: 99%
“…NSAID are known to inhibit prostaglandins and in addition, platelets aggregation, inflammation, vascular tone and permeability. 6,7 At normal or high dosages of NSAID, pulmonary capillaries are not affected, but our patient administered to himself an exceeding excessive dosage of ibuprofen whose clinical effects were unknown until that date.…”
Section: Diffuse Alveolar Damage and Acute Kidney Injury Induced By Amentioning
confidence: 85%
“…Another well-know factor is COX-2, which is an inducible enzyme. Research showed that COX-2 expressed at sites of infection, inflammation and tumor which generated prostanoids that drive disease pathogenesis 29,30 . It has been showed that COX-2 can be rapidly and robustly expressed in response to diverse range of proinflammation cytokines and mediators 31 .…”
Section: ■ Discussionmentioning
confidence: 99%